SNAP Out of It: A Study of Low-Income Families' Underutilization of Food Stamps. Issue 2 (2nd April 2016) - Cheng, Tyrone C.; Tang, Ning
ABSTRACT: The secondary data analysis examined low-income families' use of Food Stamps and how it related to receipt of Temporary Assistance to Needy Families (TANF) benefits and other financial help. It employed a nationally representative sample of 54, 703 nonelderly adults extracted from a longitudinal data set. Results showed Food Stamps utilization to be associated positively with TANF receipt; in-kind assistance; child-support receipt; number of dependent children; and being African American, female, and disabled and associated negatively with financial support from relatives/friends, family earnings, metropolitan areas, education and occupational skill, age, and being married. The findings' implications for policy and practice are discussed.